Breeding of Penta Null Soybean [Glycine max (L.) Merr.] for Five Antinutritional and Allergenic Components of Lipoxygenase, KTI, Lectin, 7S α′ Subunit, and Stachyose - Choi, Sang Woo; Ly, Sarath; Lee, Jeong Hwan; Oh, Hyeon Su; Kim, Se Yeong; Kim, Na Hyeon; Chung, Jong II (Frontiers in Plant Science, 2022)
Soybean [Glycine max (L.) Merr.] is an excellent source of protein, oil, carbohydrates and many other bioactive ingredients for humans. However, several antinutritional components also exist in the raw mature seed. Genetic removal of antinutritional and allergenic factors such as lipoxygenase, KTI, lectin, 7S α’ subunit and stachyose components would be the best method. A new soybean line with penta null recessive alleles (lox1/lox1/lox2/lox2/lox3/lox3-ti/ti-le/le-cgy1/cgy1-rs2/rs2) for these five components was developed. The breeding line has purple flowers, tawny pubescence, a determinate growth habit, and light yellow pods at maturity. The seed of the breeding line has yellow hilum and yellow seed coat color. The stem height of the breeding line was 53.0 cm. The stachyose content of the breeding line was 2.9 g/kg. The 100-seed weight of the breeding line was 31.1 g and yield (t/ha) was 2.80. This is the first soybean strain with the penta null (lox1lox2lox3/lox1lox2lox3-ti/ti-le/le-cgy1/cgy1-rs2/rs2) genotype (free of lipoxygenase, KTI, lectin, and 7S α' subunit proteins, and with low stachyose content).